The Effect Of Independence And Professional Ethics On Auditor Integrity And The Implications For Audit Quality At East Jakarta Public Accounting Firms - Elsya Meida Arif; Rozikin Rozikin; Abdi Mulya; Arni Kurniati (UNIVED Press, 2024)
The aim of this research is to examine and analyze the effec of independence and professional ethics on auditor integrity and its impact on audit quality. The data collection method uses a questionnaire with research subjects as auditors who work at KAP East Jakarta. Analysis prerequisite tests include normality test, linearity test, multicollinearity test, and heteroscedasticity test. The data analysis technique used to test the hypothesis is multiple regression analysis. Data analysis uses path analysis regression (Path analysis). The results of the research show that: 1) Independence has a positive and significant effect of 0.032 < 0.05 on auditor integrity, 2) Professional Ethics has an effect positive and significant of 0.012 < 0.05 on auditor integrity, 3) Independence has a positive and significant effect of 0.033 < 0.05 on audit quality, 4) Professional Ethics has a positive and significant effect of 0.007 < 0.05 on audit quality, 5) Auditor integrity positive and significant effect of 0.014 < 0.05 on Audit Quality, 6) integrity can be a mediator in the influence of independence on audit quality by mediation coefficient of 0.11088 (7) Integrity can be a mediator in the influence of professional ethics on audit quality with a mediation coefficient of 0.22752.